THE INFLUENCE OF CORPORATE GOVERNANCE ON RETURN ON EQUITY OF BANKS LISTED IN INDONESIA STOCK EXCHANGE (2018 – 2022 PERIOD) - Franklin Patrick Englbert; Joy Elly Tulung; Emillia Margareth Gunawan (Universitas Sam Ratulangi, 2024)
This research examines the relationship between corporate governance and Return On Equity (ROE) for Banks Listed in Indonesian Stock Exchange (IDX) from 2018 to 2022. It explores how effective corporate governance practices influence financial performance and the ability to achieve higher ROE. The study considers factors such as board structure, internal oversight practices, compensation policies, and risk management. The findings provide insights for enhancing governance practices in the face of regulatory changes, technological advancements, and increased competition. The research concludes that while the board of director partially influences ROE, and the board of commissioner partially do influence the Return On Equity but not significant the board of commissioners and directors simultaneously does have influence on ROE during the studied period. Keyword: Corporate Governance, Return On Equity, Financial Performance, Board Of Directors, Risk Management